PENGARUH STRATEGI MASS CUSTOMIZATION TERHADAP KINERJA PERUSAHAAN MELALUI PENGGUNAAN KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN (STUDI EMPIRIS PADA PERUSAHAAN BIRO WISATA DI KOTA BANDA ACEH) - Tria Ulfa; Fazli Syam BZ (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to (1) Analyze the effect of the application of mass customization strategies on company performance through the characteristics of management accounting system that are broad scope, (2) Analyze the effect of applying mass customization strategies to company performance, (3) Analyze the effect of applying mass customization strategies to the use of management accounting system information that is broad scope, (4) Analyzing the effect of the use of management accounting information systems that are broad scope on company performance. The population of this research is 126 travel companies in Banda Aceh. The sampling technique in this study was using purposive sampling techniques. This research is a study that uses primary data for his research. Primary data obtained through the distribution of questionnaires to respondents. In this study data analysis will be carried out using path analysis. The conclusions generated from this study are (1) Indirectly mass customization through the characteristics of management accounting system information has a greater positive influence on company performance, (2) Mass customization strategies have a positive influence on company performance, (3) Mass customization strategies provide positive influence on the characteristics of management accounting system information, (4) Characteristics of information management systems that are broadscope that have a positive influence on company performance